ANALISIS PRILAKU NASABAH DALAM PEMBIAYAAN DI BANK SYARIAH MANDIRI - Diah Wahyuningsih; Crisanty Sutristyaningtyas Titik; Henny Oktavianti (MediaTrend, 2014)
The main purpose of this research is to analyze customer behavior to takefinancing of sharia banking. These analyzing are: first, to know people perception aboutsharia banking. Second, to analyze the fact of customer motivation to proposefinancing. And the last, to know customer perception about riba and nisbah.This research use descriptive method base on explanatory research. Primarydata were collected by questioner and interview to customer of Bank Syari’ah MandiriBangkalan that be case study at this research.The result of this research are: first, customer perception of sharia bankingshow that majority of respondents are weakly tend (87,5%), include the comprehensionabout the kind of financing. Second, service factor (ease and speed process), believefactor, and benefit factor (less nisbah of financing). And the third is customerperception about of riba and nisbah. The answer of customer tend to see the differentboth of them from system side.